Cross‐cultural adaptation of the Arabic version of the DHEQ‐15. Issue 3 (28th January 2022) - Arheiam, Arheiam; ELTantawi, Maha; ELkadiki, Nuha; Elhashani, Abdelgader; Baker, Sarah R.
Abstract: Objectives: Many patients who suffer from Dentine Hypersensitivity (DH) often go undiagnosed because they do not consider DH as serious problem that requires treatment. The use of patient‐reported outcome measures can help in diagnosis and management of DH problems. The aim of the present study was to adapt cross‐culturally the original English version of the Dentine Hypersensitivity Experience Questionnaire (DHEQ‐15) for use in Arabic‐speaking countries. Methods: An Arabic version of DHEQ‐15 was first developed by forward‐backward translation and piloted among a group of dental patients. A cross‐sectional study design was then used to test the psychometric properties of the Arabic DHEQ‐15 in a wider convenience sample of Libyan dental patients diagnosed with DH. Confirmatory factor analysis was used to test the three‐dimensional distribution of the subscales. The significance level of all statistical tests was set at p  ≤ 0.05. Results: The Arabic DHEQ‐15 demonstrated good face and content validity. A total of 462 participants aged, on average, 39.2 ± 12.9 years took part in the psychometric testing of the Arabic DHEQ‐15. The overall Cronbach's alpha of the questionnaire was 0.91, and overall Interclass correlation coefficient (ICC) for test‐retest repeatability was 0.914. Participants with more severe DH had a significantly higher DHEQ‐15 score than those with less severe DH ( p  < 0.001). Those who reported better global rating of their oral health had lower scores on the Arabic DHEQ‐15 ( p  < 0.001). Confirmatory factor analysis confirmed three subscales of the Arabic DHEQ‐15. Conclusions: The Arabic DHEQ‐15 has been developed and further testing has demonstrated acceptable levels of psychometric properties in an Arabic population. The Arabic DHEQ‐15 is a reliable measure of the quality‐of‐life impact of DH for use with Arabic‐speaking populations.